Critical lessons : what our schools should teach - Noddings, Nel (Cambridge University Press, 2006)
Concentrating on the critical, reflective thinking that should be taught in high schools and taking seriously the Socratic advice, 'know thyself', this book focuses on topics that help students to understand the forces, good and bad, that work to socialize them. Covers issues such as war, homemaking, gender, propaganda, and religion.